(untitled) (Nigerian Journal of Physiological Sciences, 2022)
The aqueous calyx extract of Hibiscus sabdariffa (HS) is widely consumed as a beverage in Northern Nigeria and other parts of the world. HS has been reported to lower blood pressure (BP) in animals and man. However, not much is known about the effect of HS on BP in different postures. We tested the hypothesis that HS may lower BP, heart rate (HR) and heart rate-pressure product or double product (DP) by attenuating the discharge of the autonomic nervous system in different postures. Experiments were performed in accordance with the Principles of the Declaration of Helsinki. Following ethical approval and informed consent, BP and HR were measured in different postures (supine, sitting and standing) in apparently healthy human subjects (n=20) before and after (+HS) the oral administration of 15mg/Kg HS. Mean arterial pressure (MAP; taken as representative BP) and DP were calculated. Results are expressed as mean ±SEM. Paired t test and ANOVA with a post hoc Bonferroni test were used for statistical analyses. P<0.05 was considered significant. In the supine position MAP, HR and DP were significantly (P<0.0001 each) reduced in the presence of HS (85.6±1.7mmHg, 72.1±1.1/min and 8716±320mmHg.bpm) compared to its absence (89.6±2.0mmHg, 73.7±1.6/min and 8921±444mmHg.bpm). Similar trends were observed in the sitting position in the presence of HS (85.4±2.7mmHg, 73.7±1.8/min and 9098±345mmHg.bpm vs its absence: 91.4±2.3mmHg, 77.1±1.9/min and 9388±478mmHg.bpm; P<0.0001, P<0.0001 and P=0.007 respectively) and in the standing position (+HS: 89.3±2.0mmHg, 78.1±1.8/min and 10164±230mmHg.bpm vs its absence: 94.3±2.1mmHg, 81.8±2.3/min and 10742±268mmHg.bpm; P<0.0001, P<0.0001 and P=0.007 respectively). In the absence of HS, HR and DP were significantly higher in the standing posture (81.8±2.3/min, 10742±268mmHg.bpm) compared to the sitting (77.1±1.9/min, 9388±478mmHg.bpm; P<0.05 and P<0.0001 respectively) and the supine (73.7±1.6/min, 8921±444mmHg.bpm; P<0.001 each) postures while the BP remained similar. A similar trend was observed across the three postures in the presence of HS although the parameters were significantly lower. It is concluded that HS lowered BP, HR and DP by modulating autonomic mechanisms through the inhibition of both parasympathetic withdrawal and sympathetic nervous system discharge across the postures. Also the standing posture is associated more with a higher sympathetic nervous system discharge and a higher cardiac oxygen demand and workload than the sitting and supine postures in the absence or presence of HS.